Perception on terrorist, awarness and attitude of police officers in Iloilo City towards terrorism. - Layog, Baby Lyn R. (2016.)
This study aimed to determine the police officers perception on terrorism, their basic knowledge towards terrorism in international and national level, and their behavioral tendencies on terrorism-related activities. Majority of the respondents describe the demographic profiles of possible terrosts as more likely to be adolescents, single, Muslim, and Middle-eastern descent. The results also revealed the usual depiction of terrorism-related activities is the creation of fear often instigated by economic and political interest, often targets ordinary citizens are prevalent both in international and national level. In addition, respondents acquire their basic knowledge in terrosim through different forms of media both in national and international level. However, respondents verified the reported news within the country through reading the official statement release by the Philippoine National Police (PNP). On the other hand, the positive and negative attitude of the respondents in different situations regarding terrorism-related activities heavily rely on their personal axperiences.
Research project -- Bachelor of Arts (Psychology-History). University of the Philippines Visayas, Iloilo.
Keywords: Terrosim; Police Officers; Perception -- Terrorism; Awareness -- Terrorism